Atypical Presentation of Mycosis Fungoides- A Rare Case Report - Wahab, MA; Rahaman, Md Mahabubur; Warish, Nehal; Quader, Md Rezaul; Rahman, M Hasibur (Community Based Medical Journal, 2015)
Commonest cutaneous T cell lymphoma is mycosis fungoides. Clinical stages are patch, plaque, tumor; erythroderma and poikoiloderma. Extracutaneous spread takes place in late stages where any organ may be involved. The majority of reported cases are with typical presentation. A rare case of mycosis fungoides in a 45-year-old male with papular eruption is described. CBMJ 2015 July: Vol. 04 No. 02 P: 62-64